Use of baby food products during the complementary feeding period: What factors drive parents' choice of products? - Grace Hollinrake; Sophia Komninou; Amy Brown (Wiley, 2024)
Abstract It is recommended that infants are introduced to complementary foods from 6 months old, moving from a solely milk diet to eating a family diet by 12 months old. Although home cooking of family foods is recommended, a rapidly growing market producing baby food products (BFP) such as jars, pouches and snacks has developed. These are often accompanied by marketing claims around nutritional, health and developmental impacts despite research highlighting high sugar content. Although numerous studies have explored drivers of infant formula choice and use, little research has examined the drivers of BFP use. This study used an online survey for United Kingdom parents of infants aged 4-12 months to explore use of BFP alongside perceptions and drivers to purchase products. Overall, 271 parents participated (173 used BFP and 98 did not), with a descriptive analysis of closed items and a thematic analysis for open ended text conducted. The top motivators for using BFP were convenience, time saving, and baby's perceived enjoyment of products. The most purchased puree was fruit based and the most purchased baby snacks were vegetable puffs/sticks, with snack purchases being more common than purees in this sample. Aspects such as perceived healthiness drove choice, with snack foods being seen to enhance self‐feeding skills, appetite regulation and motor development. Those who did not use BFP did not trust them and preferred to feed their baby home cooked foods. The findings are important for professionals working with parents, to support them through the transition to solid foods, particularly around raising awareness of marketing techniques and how to check content of foods to make a more informed choice.